Technical-tactical actions to improve the effectiveness of the forward hand in boxers - Yusmel García Raveiro; Rosa María Tabares Arévalo; Girardo Machuat Santana (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
Sports training is a pedagogical process aimed at achieving adequate preparation of the athlete and systematically controlling his or her evolution. Boxing as a combat sport requires precise actions in a very short period of time because if one is faster in the technical action in the attacks, it is impossible to defend and counterattack. Hence the importance of working with the forward hand to win a fight. Therefore, the objective of this study is to propose a set of technical-tactical actions to contribute to the improvement of the work with the forward hand, the face and the trunk of the first category boxers of the Provincial Boxing Academy of Pinar del Río. A sample of five coaches and ten athletes was selected; all of them belong to the first category team of the Provincial Academy of Pinar del Río. Theoretical and empirical research methods were used, such as historical-logical, analysis-synthesis, systemic-structural, document review, interview, survey, observation and descriptive statistics. The actions are based on five basic premises and three moments of the training session, according to the technique to be executed, offering general orientations, exercises for the improvement (from the boxing school, from the combat school and from the fixed and hanging apparatus) and how to carry out the control. The theoretical evaluation by specialists and a practical application of three months corroborate that the proposal was effective.